The Influence Work Overload And Job Stress Through Preceived Organization Support On Job Performance At Pos Regional Vi Makassar Employee - Denny Aprianto; Idayanti Nursyamsi; Ria Mardiana Y (Jurnal Mirai Management, 2023)
This study aims to determine the effect of Work Overload and Job Stress Through Perceived Organizational Support on Job Performance at POS Regional VI Makassar Employees. This research is quantitative descriptive. The sample in this study were Oranger POS Regional VI Makassar which was divided into 2 offices, namely the Makassar main branch office and SPP Makassar with a total sample of 81 respondents consisting of mobile orangers, delivery oranges and counter oranges. The data sources used are primary data and secondary data. Data was collected by distributing questionnaires with validity and reliability tests on all statement items. Data processing uses the application of Statistical product and service solution (SPSS) version 25 and path analysis to test the significance of the direct and indirect effects between variables using the Sobel test and the results are significant. The results showed that all variables had a positive and significant effect and the highest coefficient value was 0.683, the indirect effect of Job Strees on Job Performance through Perceived Organization Support and the lowest, namely 0.347 The Direct Effect of Work Overload on Job Performance. Keywords: Work Overload, Job Stress, Perceived Organizational Support, Job Performance.